Sputum Smear Microscopy for Tuberculosis: Evaluation of Autofocus Functions and Automatic Identification of Tuberculosis Mycobacterium - Filho, Cicero F. F. Costa; Costa, Marly G. F. (IntechOpen, 2012)
None